(untitled) (Journal of Public and Nonprofit Affairs, 2021)
This article explores how the intersections of gender, place, and race impact the socially equitable application of criminal justice administration in Alabama. Specifically, most re-entry programs fail to address the varied and unique post-carceral needs of Black women. As such, this work examines the obstacles and opportunities for non-profit re-entry program administrators who seek to uphold the civil and human rights of Black women and highlights best practices in providing meaningful re-entry and reintegration services to women from historically under-resourced communities. Using social equity’s theoretical principles in criminal justice, this article spotlights Alabama’s re-entry programs and explores what occurs at the juncture of social equity, community-based criminal justice administration, and recidivism; this article also illustrates the interconnectedness of these three concepts.